Relationship Between Serum Albumin and Risk of Atrial Fibrillation: A Dose-Response Meta-Analysis - Wang, Yali; Du, Peng; Xiao, Qi; Li, Jianfeng; Liu, Xiao; Tan, Jinfeng; Zhang, Xingjian (Frontiers in Nutrition, 2021)
Background: The dose-response association between serum albumin and atrial fibrillation is not well known. This study aims to assess the relationship between albumin and atrial fibrillation and the potential dose-response effect. Methods: Studies reported the serum albumin and AF were identified through searching EMBASE, PubMed, and the Cochrane Library database. The potential dose-response effect was performed using a stage robust error meta-regression. Results: Nine studies were included, with a total of 32,130 individuals. High albumin level was associated with decreased risk of atrial fibrillation compared with the patients with the low serum albumin (OR[odds ratio]: 0.62, 95% CI [0.44, 0.89]; I2=76%; P=0.009). In the dose-response analysis, for each 10 g/L increase in serum albumin level, the risk of atrial fibrillation decreased by 36% (95% CI: 0.51–0.81, I2=87%, P<0.001). Furthermore, a significant positive linear relationship between serum albumin and the risk of atrial fibrillation (Pnonlinearity=0.33) was found. Conclusion: Our dose-response meta-analysis suggests low serum albumin level is associated with an increased risk of atrial fibrillation. Further studies are needed to explore the effect of induction of elevated serum albumin levels on the prevention of atrial fibrillation.